Pengaruh Inflasi, Institutional Ownership dan Managerial Ownership Terhadap Financial Performance pada Perusahaan Sektor Rokok yang Terdaftar di Bei - Azmi, M. Rafif; Zahrah, Zahrah; Nirwana, Baiq Nadia; Hendri, Wira; Marswandi, Ega Dwi Putri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The cigarette industry is undergoing rapid change and contributes significantly to Indonesia's national income through excise taxes. However, the cigarette industry faces challenges from the macroeconomy and pressure from the government, such as regulatory pressure, health policies, tightening regulations on cigarettes, and annual increases in excise taxes, which put pressure on the cigarette industry in Indonesia. The purpose of this study is to examine and analyze the partial effects of inflation, institutional ownership, and managerial ownership on the financial performance of tobacco companies listed on the Indonesia Stock Exchange (IDX). Additionally, the study aims to examine and analyze the simultaneous effects of inflation, institutional ownership, and managerial ownership on the financial performance of tobacco companies listed on the IDX. The type of research used is associative causal with a quantitative approach, and the analysis technique used is panel data involving four tobacco companies over an eight-year observation period from 2017 to 2024. The sample data was processed using E-Views 12, totaling 32 samples. The results show that inflation has no partial effect on financial performance. Meanwhile, institutional ownership and managerial ownership have a partial positive effect on financial performance. Simultaneous testing shows that the three independent variables in this study have a simultaneous effect on financial performance.